Nickel-based single-crystal high-temperature alloy and preparation method thereof

By optimizing the chemical composition and heat treatment of nickel-based single-crystal superalloys and reducing the γ/γ′ phase interface energy, the limitations of Re-free second-generation single-crystal superalloys in terms of high-temperature strength and microstructure stability have been overcome, realizing a low-cost, high-performance single-crystal superalloy.

CN120924836APending Publication Date: 2025-11-11RED SILVER METAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510924295.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-04
Publication Date
2025-11-11

AI Technical Summary

Technical Problem

Existing Re-free second-generation single-crystal superalloys have limitations in improving high-temperature strength and microstructure stability, especially due to the high γ/γ′ phase interface energy, making it difficult to further improve high-temperature mechanical properties through γ/γ′ phase interface strengthening.

Method used

By optimizing the chemical composition design of nickel-based single-crystal superalloys and controlling the proportions of Co, W, Ta, Mo, and Cr elements to achieve (Co+W+Ta)/(Mo+Cr) = 2.9–3.1, and combining this with appropriate heat treatment regimes, including solution treatment and aging treatment, a Re-free second-generation single-crystal superalloy with low γ/γ′ phase interface energy was prepared.

Benefits of technology

It achieves low interfacial energy and good microstructure stability in Re-free second-generation single-crystal superalloys, significantly improving high-temperature mechanical properties, with a creep life exceeding 150 hours, and at a lower cost than traditional Re-containing alloys.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120924836A_ABST
    Figure CN120924836A_ABST
Patent Text Reader

Abstract

The invention relates to a nickel-based single-crystal high-temperature alloy and a preparation method thereof, and relates to the technical field of nickel-based single-crystal high-temperature alloys, and the main technical scheme is as follows: the nickel-based single-crystal high-temperature alloy comprises the following chemical components in percentage by weight: 6-8 wt% of Cr, 7-9 wt% of Co, 2-3 wt% of Mo, 8-9 wt% of W, 5-7 wt% of Ta, 5-7 wt% of Al, 1-2 wt% of Ti, 0-0.05 wt% of C and the balance of Ni; wherein the sum of the percentage contents of the Co element, the W element and the Ta element is A; the sum of the percentage contents of the Mo element and the Cr element is B; wherein A / B is equal to 2.9 to 3.1. The invention mainly provides and prepares a nickel-based single-crystal high-temperature alloy, and the alloy has low gamma / gamma'phase interface energy and good long-term structure stability, and also has high-temperature mechanical properties obviously superior to those of typical second-generation Re-containing single-crystal high-temperature alloys.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of nickel-based single-crystal superalloy technology, and in particular to a nickel-based single-crystal superalloy and its preparation method. Background Technology

[0002] The development of technologies such as aero-engines, marine gas turbines, and ground-based gas turbines demands that single-crystal superalloys used in engine turbine blades possess excellent high-temperature strength and structural stability, while also having low operating and maintenance costs. Currently, the addition of rare and precious metals such as Re and Ru has significantly improved the strength of the γ-matrix phase in single-crystal superalloys, restricting dislocation movement within the matrix and thus significantly enhancing the high-temperature strength of the alloy. However, the high price of elements like Re and Ru hinders the sustainable development of single-crystal superalloys. Therefore, there is an urgent need to develop low-cost, high-performance single-crystal superalloys that do not contain rare and precious elements such as Re and Ru.

[0003] Currently, Chinese researchers have developed a series of Re-free second-generation nickel-based single-crystal superalloys, such as DD98M, DD13, DD413M, and M09A, by increasing the volume fraction of the γ′ phase. The high-temperature performance of these alloys is similar to that of traditional Re-containing second-generation single-crystal superalloys, but the γ′ phase volume fraction is already as high as 68%-72%, making it impossible to further improve their high-temperature strength by increasing the γ′ phase volume fraction. Furthermore, the amount of γ-phase solid solution elements added has reached its limit to avoid the formation of harmful phases such as TCP. Therefore, precipitation strengthening and solid solution strengthening of Re-free second-generation single-crystal superalloys have reached their limits, and there is an urgent need to explore new strengthening methods to further improve the high-temperature strength and microstructure stability of this alloy system.

[0004] γ / γ′ phase interface strengthening is another important strengthening mechanism for single-crystal superalloys. A stable low-energy γ / γ′ phase interface can delay γ′ phase growth during service, reduce the γ′ phase rafting rate, and effectively improve its resistance to dislocations at high temperatures. Furthermore, the low-energy phase interface has a higher dislocation mobility to bypass the barrier, resulting in a larger dislocation density at the γ / γ′ phase interface, which can further hinder dislocation movement from the matrix and improve its high-temperature strength. Therefore, the high-temperature mechanical properties of low-cost Re-free single-crystal superalloys can be further improved through γ / γ′ phase interface strengthening. However, currently, there are very few high-strength single-crystal superalloys in China that utilize γ / γ′ phase interface control.

[0005] In summary, there is an urgent need for a Re-free second-generation single-crystal superalloy with a low γ / γ′ phase interface energy, so that the single-crystal superalloy can have excellent high-temperature mechanical properties and microstructure stability. Summary of the Invention

[0006] In view of this, the present invention provides a nickel-based single-crystal superalloy and its preparation method, the main purpose of which is to provide a Re-free second-generation single-crystal superalloy with lower γ / γ′ phase interface energy.

[0007] To achieve the above objectives, the present invention mainly provides the following technical solutions:

[0008] On one hand, embodiments of the present invention provide a nickel-based single-crystal superalloy, wherein, by weight percentage, the nickel-based single-crystal superalloy comprises the following chemical composition:

[0009] Cr: 6-8 wt%, Co: 7-9 wt%, Mo: 2-3 wt%, W: 8-9 wt%, Ta: 5-7 wt%, Al: 5-7 wt%, Ti: 1-2 wt%, C: 0-0.05 wt%, balance Ni;

[0010] The sum of the percentage contents of Co, W, and Ta is A; the sum of the percentage contents of Mo and Cr is B; and A / B = 2.9 to 3.1.

[0011] Preferably, the nickel-based single-crystal superalloy comprises the following chemical composition by weight percentage:

[0012] Cr: 6.0~7.8wt%, Co: 7.5~8.9wt%, Mo: 2.0~2.6wt%, W: 8.3~8.9wt%, Ta: 5.5~6.8wt%, Al: 5.3~6.7wt%, Ti: 1.7~1.8wt%, C: 0.02~0.04wt%, the balance is Ni.

[0013] Preferably, in the nickel-based single-crystal superalloy: the number of electron vacancies N v ≤2.3. It should be noted that electron vacancies are primarily used to assess the microstructure stability of the alloy and predict the potential formation of precipitated phases, especially the precipitation trend of the TCP phase. When Nv ≤ 2.3, the TCP phase is less likely to form in the alloy, and the γ′ phase microstructure is stable.

[0014] Preferably, in the nickel-based single-crystal superalloy, the weight percentage content of impurity elements meets the following requirements:

[0015] O≤0.001wt%, N≤0.001wt%, S≤0.001wt%, Zr≤0.0055wt%, Mn≤0.01wt%, Si≤0.005wt%, P≤0.005wt%, Cu≤0. 05wt%, Mg≤0.008wt%, Se≤0.0002wt%, Pb≤0.0002wt%, Te≤0.00005wt%, Bi≤0.00002wt%, Sn≤0.0015wt%.

[0016] Preferably, if the nickel-based single-crystal superalloy is in a heat-treated state, then the γ / γ′ interfacial energy E in the nickel-based single-crystal superalloy is less than 5 × 10⁻⁶. -2 J / m 2 The γ′ opposite domain boundary energy is >250 mJ / m 2 .

[0017] Preferably, the nickel-based single-crystal superalloy is a Re-free second-generation single-crystal superalloy; and / or if the nickel-based single-crystal superalloy is in a heat-treated state, the creep rupture life of the nickel-based single-crystal superalloy under the conditions of 1100℃±5℃ and 137MPa±5MPa is >150h; and / or if the nickel-based single-crystal superalloy is in a heat-treated state, after heat exposure treatment at 900-1100℃ for 200-300h, the γ′ phase still exhibits a cubic shape, thus improving the creep rupture life; more preferably, before heat exposure, the creep rupture life of the nickel-based single-crystal superalloy under the conditions of 1100℃±2℃ and 127MPa±2MPa is 120h±10h, and after heat exposure treatment, the creep rupture life of the nickel-based single-crystal superalloy under the conditions of 1100℃±2℃ and 127MPa±2MPa is 150h±10h. The mechanical properties did not deteriorate; on the contrary...

[0018] Preferably, the preparation method includes the following steps:

[0019] Vacuum induction melting step: The raw materials are subjected to vacuum induction melting and cast into master alloy ingots;

[0020] The steps for preparing single-crystal alloys are as follows: the master alloy ingot is remelted by high-speed solidification or liquid metal cooling, and then directional solidification is performed by spiral crystal selector or seed crystal method to obtain cast nickel-based single-crystal high-temperature alloy.

[0021] Heat treatment: The cast nickel-based single-crystal superalloy is subjected to heat treatment to obtain a heat-treated nickel-based single-crystal superalloy.

[0022] Preferably, in the vacuum induction melting step: the raw materials include elemental Ni, elemental Co, elemental Cr, elemental W, elemental Mo, elemental Ta, elemental Ti, elemental Al, and elemental C; and / or in the vacuum induction melting, the refining temperature is 1550±10℃, the refining time is 20~40min, and the vacuum degree during refining is ≤5Pa.

[0023] Preferably, in the single-crystal alloy preparation step: the casting temperature is 1530–1560°C; and / or the directional solidification pulling rate is 3–7 mm / min.

[0024] Preferably, the heat treatment step includes:

[0025] Solution treatment steps: The as-cast nickel-based single crystal high-temperature alloy is first heated to 1285-1295℃ and held for 2-3 hours, then heated to 1295-1300℃ and held for 2-5 hours, then heated to 1325-1350℃ and held for 3-5 hours, and then cooled to obtain the solution-treated nickel-based single crystal high-temperature alloy.

[0026] Aging treatment steps: The solution-treated nickel-based single-crystal superalloy is first heated to 1085-1095℃, held for 5-7 hours, and then cooled to room temperature; then heated to 850-879℃, held for 22-26 hours, and cooled to obtain the heat-treated nickel-based single-crystal superalloy.

[0027] Compared with the prior art, the nickel-based single-crystal superalloy and its preparation method of the present invention have at least the following beneficial effects:

[0028] On one hand, embodiments of the present invention provide a nickel-based single-crystal superalloy, which, by weight percentage, comprises the following chemical composition: Cr: 6-8 wt%, Co: 7-9 wt%, Mo: 2-3 wt%, W: 8-9 wt%, Ta: 5-7 wt%, Al: 5-7 wt%, Ti: 1-2 wt%, C: 0-0.05 wt%, with the balance being Ni. Here, the above composition design achieves two main effects: firstly, a lower interfacial energy ensures the structural stability of the γ' phase in the alloy; secondly, it enhances the anti-domain boundary energy of the γ' phase, thereby improving its resistance to dislocation shear. Based on this, the percentage content of Co, W, Ta, Mo, and Cr must satisfy the following: (Co+W+Ta) / (Mo+Cr) = 2.9–3.1. This design results in a low γ / γ' phase interface energy in the nickel-based single-crystal superalloy, allowing for a well-formed cubic γ' phase morphology even during high-temperature aging. Furthermore, the alloy exhibits low mismatch within its service temperature range, leading to a slower γ' phase degradation rate. In summary, through the above compositional design, the alloy achieves low γ / γ′ phase interface energy and good long-term structural stability, while also possessing significantly superior high-temperature mechanical properties compared to typical second-generation Re-containing single-crystal superalloys.

[0029] On the other hand, the present invention provides a method for preparing the above-mentioned nickel-based single-crystal high-temperature alloy. Here, by designing a suitable heat treatment regime, it is conducive to the uniform diffusion of large-sized atoms such as W, Mo and Ta, so as to realize the preparation of Re-free second-generation single-crystal alloy.

[0030] In summary, the nickel-based single-crystal superalloy and its preparation method provided by the embodiments of the present invention result in a nickel-based single-crystal superalloy with a low γ / γ′ phase interface energy, approximately 70% of that of the Rene N5 alloy in the heat-treated state. Furthermore, the alloy of the present invention does not contain the precious element Re, yet its creep rupture performance is significantly superior to that of the Rene N5 single-crystal superalloy, exhibiting a creep rupture life >150h at 1100℃ / 137MPa and >100h at 1100℃ / 235MPa, classifying it as an ultra-high-strength, low-cost single-crystal superalloy. Under long-term heat exposure conditions of 900-1000℃, the alloy of the present invention maintains stable microstructure, and its mechanical properties do not deteriorate after prolonged heat exposure; on the contrary, they significantly improve.

[0031] The above description is merely an overview of the technical solution of the present invention. In order to better understand the technical means of the present invention and to implement it in accordance with the contents of the specification, the preferred embodiments of the present invention are described in detail below with reference to the accompanying drawings. Attached Figure Description

[0032] Figure 1 Microstructure of the heat-treated nickel-based single-crystal superalloy prepared in Example 1;

[0033] Figure 2 This is a schematic diagram of the γ / γ′ phase interface mismatch of the heat-treated nickel-based single-crystal superalloy prepared in Example 2;

[0034] Figure 3 Comparison of γ / γ′ phase interface energies between the heat-treated nickel-based single-crystal superalloy prepared in Example 3 and typical heat-treated second-generation nickel-based single-crystal superalloys Rene N5, CMSX-4, PWA1484 and DD406.

[0035] Figure 4 This is a comparison chart of Larson-Miller curves of the heat-treated nickel-based single-crystal superalloy prepared in Example 4 and the typical heat-treated second-generation nickel-based single-crystal superalloy Rene N5.

[0036] Figure 5 These are creep performance diagrams of the heat-treated nickel-based single-crystal superalloy prepared in Example 5 after different long-term heat exposures at 900°C.

[0037] Figure 6 The microstructure of the heat-treated nickel-based single-crystal superalloys prepared in Example 1 and Comparative Example 1 after holding at 1100℃ for 200h is shown.

[0038] Figure 7 The microstructure of the heat-treated nickel-based single-crystal superalloys prepared in Example 1 and Comparative Example 2 after being held at 1100℃ for 200h is shown.

[0039] Figure 8 The microstructure of the heat-treated nickel-based single-crystal superalloys prepared in Example 1 and Comparative Example 3 after being held at 1100°C for 300 hours is shown. Detailed Implementation

[0040] To further illustrate the technical means and effects adopted by the present invention to achieve the intended purpose, the specific embodiments, structures, features, and effects according to the present invention will be described in detail below with reference to the accompanying drawings and preferred embodiments. In the following description, different "embodiments" or "embodiments" do not necessarily refer to the same embodiment. Furthermore, specific features, structures, or characteristics in one or more embodiments can be combined in any suitable form.

[0041] This invention provides a nickel-based single-crystal superalloy and its preparation method. This alloy has low γ / γ′ phase interface energy and good long-term microstructure stability, and also has high-temperature mechanical properties that are significantly better than those of typical second-generation Re-containing single-crystal superalloys.

[0042] On one hand, embodiments of the present invention provide a nickel-based single-crystal superalloy, wherein the nickel-based single-crystal superalloy comprises the following chemical composition by weight percentage:

[0043] Cr: 6–8 wt%, Co: 7–9 wt%, Mo: 2–3 wt%, W: 8–9 wt%, Ta: 5–7 wt%, Al: 5–7 wt%, Ti: 1–2 wt%, C: 0–0.05 wt%, balance Ni;

[0044] The sum of the percentage contents of Co, W, and Ta is A; the sum of the percentage contents of Mo and Cr is B; and A / B = 2.9 to 3.1; that is, (Co+W+Ta) / (Mo+Cr) = 2.9 to 3.1.

[0045] The above component design is explained as follows:

[0046] 1) Al is the most important precipitation-strengthening γ' phase forming element, ensuring that the volume fraction of the γ' phase in single-crystal superalloys is between 60% and 70%, thus guaranteeing the precipitation strengthening effect of the single-crystal alloy. Therefore, the Al content in Re-free second-generation single-crystal superalloys is 5–7 wt%, preferably 5.3–6.7%.

[0047] 2) Ti is also the most important precipitation-strengthening γ' phase forming element. In addition, Ti can also increase the antiphase domain boundary energy of the γ' phase and improve the high-temperature strength of the alloy. However, if the Ti content is too high, the alloy microstructure stability is poor, and the eutectic content is high, making the heat treatment of the alloy extremely difficult. Considering the above factors, the present invention controls the Ti content to be 1-2 wt%, preferably 1.7-1.8 wt%.

[0048] 3) Co and Ni are completely miscible, and Co significantly reduces the stacking fault energy of the matrix, making cross-slip of screw dislocations extremely difficult. This hinders the movement barrier of dislocations at the γ / γ′ phase interface, improving the high-temperature stability of the γ / γ′ phase interface. However, high-Co alloys also promote TCP phase precipitation, and excessively high Co content can lower the solid solution temperature, leading to a decrease in the high-temperature performance of the alloy. Therefore, this invention controls the Co content at 7–9 wt%, or 7.5–8.9 wt%.

[0049] 4) W is the most important solid solution strengthening element in high-temperature alloys, and its proportions in the γ and γ′ phases are similar, which can effectively reduce the chemical potential gradient at the γ / γ′ phase interface, suppress the coarsening of the γ′ phase at high temperatures, and delay the migration rate of the γ / γ′ phase interface. However, W promotes the formation of the TCP phase, which is very detrimental to the microstructure stability of the alloy. Therefore, the W content in the alloy of this invention is controlled at 8-9 wt%, preferably 8.3-8.9 wt%.

[0050] 5) Mo increases the content of elements such as Mo and Cr in the γ phase, which improves the γ / γ′ lattice mismatch of the single-crystal alloy and is detrimental to the high-temperature microstructure stability of the alloy. Furthermore, increased Mo content leads to the precipitation of the TCP phase. Therefore, the Mo content in the alloy of this invention is controlled at 1–3 wt%, preferably 2–2.6 wt%.

[0051] 6) Ta is the most important precipitation-strengthening γ' phase-forming element in high-temperature alloys. The addition of Ta increases the strength of the γ' phase in the alloy, ensuring a good cubic morphology and low misfit at high temperatures, significantly slowing down the γ' phase rafting rate. However, excessive Ta leads to the formation of a large amount of eutectic in the as-cast microstructure. This eutectic structure cannot be fully dissolved during subsequent heat treatment, leaving a large amount of residual eutectic and deteriorating the alloy's mechanical properties. Therefore, the Ta content in the alloy of this invention is controlled at 5–7 wt%, preferably 5.5–6.8 wt%.

[0052] 7) While Cr ensures excellent high-temperature oxidation resistance in single-crystal superalloys, its solid solution strengthening effect is relatively weak. A high Cr content limits the addition of other solid solution strengthening elements (W, Mo, Ta, Re, etc.), increases the chemical potential gradient of the solid solution elements across the γ / γ′ phase interface, leading to instability at the γ / γ′ phase interface and deteriorating its high-temperature performance. Therefore, the composition design of high-strength, Re-free second-generation single-crystal superalloys with low γ / γ′ phase interface energy requires a moderately reduced Cr content, ideally 6–8 wt%, preferably 6–7.8 wt%.

[0053] 8) The addition of an appropriate amount of C can improve the alloy's processing performance and defect tolerance. However, the addition of excessive C will reduce the alloy's performance. Therefore, the present invention controls the C content to 0-0.05 wt%, preferably 0.02-0.04 wt%.

[0054] 9) Preferably, the nickel-based single-crystal superalloy comprises the following chemical composition by weight percentage:

[0055] Cr: 6.0~7.8wt%, Co: 7.5~8.9wt%, Mo: 2.0~2.6wt%, W: 8.3~8.9wt%, Ta: 5.5~6.8wt%, Al: 5.3~6.7wt%, Ti: 1.7~1.8wt%, C: 0.02~0.04wt%, the balance is Ni.

[0056] 10) Based on the above, this invention, through extensive research, has discovered that when (Co+W+Ta) / (Mo+Cr) = 2.9–3.1, the γ / γ' phase interfacial energy in the alloy is relatively low. High-temperature aging still yields a γ' phase morphology with good cubicity, and the alloy exhibits low mismatch within its service temperature range, thus resulting in a slower γ' phase degradation rate. The principle is as follows:

[0057] a. When (Co+W+Ta) / (Mo+Cr) = 2.9~3.1, the alloy has a low γ / γ' phase interfacial energy and excellent microstructural stability. The most significant effect on alloy properties is the improvement in its high-temperature microstructural stability. The γ' phase in the alloy does not undergo rafting, and the low-energy, high-strength interface effectively blocks dislocation movement from the matrix, thus improving high-temperature creep resistance.

[0058] b. The elements in the above formula have a synergistic effect. The specific synergistic principle is in the following three aspects: (1) Interaction between electron filling and band structure: For example, Cr and Mo, as transition metals, can form a specific electron filling mode in alloys or compounds, affecting the electronic structure of other elements such as Co and W, improving the stability of each element, mutually inhibiting the diffusion ability of each element, and thus improving the structural stability of the material; (2) Matching of atomic size and radius: The atomic radii of Co and W are similar to those of Mo and Cr. Elements such as Co and W can synergize with Mo and Cr through their atomic size and radius, control their relative content, and further inhibit the diffusion of elements; (3) Dissolution diffusion and solid solution strengthening: W and Ta will anomalously accumulate in the γ′ phase during long-term heat exposure. Therefore, by adding Co to balance the γ phase forming elements Mo and Cr, the antiphase domain boundary energy of the γ′ phase is guaranteed, and the high-temperature structural stability and mechanical properties of the alloy are improved.

[0059] On the other hand, embodiments of the present invention also provide a method for preparing a nickel-based single-crystal superalloy, which mainly includes the following steps:

[0060] 1) Vacuum induction melting step: The raw materials are subjected to vacuum induction melting and cast into master alloy ingots.

[0061] In this step: the nickel-based single crystal high-temperature alloy of the present invention is smelted in a vacuum induction furnace using pure Ni, Co, Cr, W, Mo, Ta, Ti, Al, C and other elements (refining temperature: 1550±10℃, refining time 30min, vacuum degree during refining ≤5Pa), and then cast into a master alloy ingot with the required chemical composition.

[0062] 2) Preparation of single crystal alloy: The master alloy ingot is remelted by high-speed solidification or liquid metal cooling, and then directional solidification is performed by spiral crystal selector or seed crystal method to obtain cast nickel-based single crystal high temperature alloy.

[0063] The master alloy ingot is remelted by high-speed solidification or liquid metal cooling (cast at 1550℃±10℃, with a directional solidification pulling rate of 3~7mm / min, preferably 5mm / min), and then directionally solidified into a single crystal specimen using a spiral crystal selector or seed crystal method (preferably, to form a single crystal specimen). <001> Oriented single crystal test rods).

[0064] 3) Heat treatment: The as-cast nickel-based single-crystal superalloy is subjected to heat treatment to obtain a heat-treated nickel-based single-crystal superalloy. The heat treatment steps include:

[0065] Solution treatment steps: The as-cast nickel-based single crystal high-temperature alloy is first heated to 1285-1295℃ and held for 2-3 hours, then heated to 1295-1300℃ and held for 2-5 hours, then heated to 1325-1350℃ and held for 3-5 hours, and then cooled to obtain the solution-treated nickel-based single crystal high-temperature alloy.

[0066] Aging treatment steps: The solution-treated nickel-based single-crystal superalloy is first heated to 1085-1095℃, held for 5-7 hours, and then cooled to room temperature; then heated to 850-879℃, held for 22-26 hours, and cooled to obtain the heat-treated nickel-based single-crystal superalloy.

[0067] One of the preferred heat treatment regimes is as follows:

[0068] 1290℃ / 2h+1295℃ / 2h+1300℃ / 4h / AC+1090℃ / 6h / AC+870℃ / 24h / AC (AC: air cooling).

[0069] In addition, air cooling is selected as the cooling method in the heat treatment process.

[0070] In addition, it should be noted that:

[0071] (1) Compared with the conventional heat treatment system for second-generation single-crystal alloys, the heat treatment system of the present invention has a higher solution treatment temperature and a longer solution treatment time, which is conducive to the uniform diffusion of large-sized atoms such as W, Mo and Ta. It increases the number of γ′ phases and the internal antiphase domain boundary energy, thereby increasing the resistance of dislocations to cutting through the γ′ phase.

[0072] Meanwhile, the heat treatment process can ensure the cubicity of the γ′ phase and further reduce the phase interface mismatch, thereby improving the microstructure stability and mechanical properties.

[0073] (2) This invention mainly achieves the preparation of Re-free second-generation single crystal alloys through composition optimization and heat treatment system optimization.

[0074] (3) This invention develops a high-strength Re-free second-generation single-crystal high-temperature alloy with low γ / γ′ phase interface energy. Its cost is lower than that of the traditional second-generation single-crystal high-temperature alloy Rene N5, its mechanical properties are significantly better than those of Rene N5, and the alloy has excellent static and dynamic structural stability.

[0075] Compared with other existing high-strength nickel-based single-crystal superalloys, the alloy of this invention has a lower γ / γ′ phase interface energy, and the γ / γ′ phase interface energy in the heat-treated state is about 70% of that of Rene N5 alloy.

[0076] The alloy of this invention does not contain the precious element Re, but its creep rupture performance is significantly better than that of Rene N5 single-crystal superalloy. It exhibits a creep rupture life of >150h at 1100℃ / 137MPa and >100h at 1100℃ / 235MPa, making it an ultra-high strength, low-cost single-crystal superalloy.

[0077] The alloy of the present invention exhibits stable microstructure under long-term heat exposure at 900-1000℃. The mechanical properties of the alloy do not deteriorate after long-term heat exposure, but rather improve significantly. (It should be noted that: (1) After long-term heat exposure for 200-300h, the alloy microstructure is stable, specifically the γ′ phase remains cubic. If the microstructure is unstable, the γ′ phase will raft. (2) Before heat exposure, the creep life under 1100℃ / 127MPa conditions is about 120h. After heat exposure for 200-300h, it can reach about 150h. (3) The reason for the improved mechanical properties after heat exposure is that the alloy has a highly stable phase interface. The phase interface energy of the alloy of the present invention is low, and it is very stable during high-temperature service, which ensures the stability of the interface and the γ′ phase. At the same time, high temperature promotes the diffusion of elements such as W and Ta into the γ′ phase, which increases the antiphase domain boundary energy and improves the ability to resist dislocation movement.)

[0078] The following preferred experimental examples further illustrate this point:

[0079] Example 1

[0080] This embodiment prepares a nickel-based single-crystal superalloy, the chemical composition of which is shown in Table 1. The main preparation steps are as follows:

[0081] 1) The raw materials are vacuum induction melted and cast into master alloy ingots that conform to the chemical composition.

[0082] The raw materials include elemental metals Ni, Co, Cr, W, Mo, Ta, Ti, Al, and C.

[0083] In vacuum induction melting, the refining temperature is 1550℃, the refining time is 40min, and the vacuum degree during refining is ≤5Pa.

[0084] 2) The master alloy ingot was remelted by high-speed solidification and then directional solidification was performed using a spiral crystal selector to obtain a cast nickel-based single crystal superalloy (single crystal test rod).

[0085] Specifically, the master alloy ingot is grown into single crystals in a high-temperature gradient directional solidification furnace (growth rate of 5 mm / min), and then processed using a spiral crystal selection method. <001> Oriented single crystal test rods.

[0086] 3) The single crystal test rods were subjected to solution treatment and aging treatment to obtain heat-treated nickel-based single crystal high-temperature alloys.

[0087] The solution treatment conditions were: 1290℃ / 2h + 1295℃ / 2h + 1300℃ / 4h, AC (air cooling).

[0088] The aging process is as follows: 1090℃ / 6h, AC+870℃ / 24h, AC (air cooling).

[0089] Example 2

[0090] This embodiment prepares a nickel-based single-crystal superalloy, the chemical composition of which is shown in Table 1. The difference between this embodiment and Example 1 lies in the chemical composition. Other preparation steps and parameters are the same as in Example 1.

[0091] Example 3

[0092] This embodiment prepares a nickel-based single-crystal superalloy, the chemical composition of which is shown in Table 1. The difference between this embodiment and Example 1 lies in the chemical composition. Other preparation steps and parameters are the same as in Example 1.

[0093] Example 4

[0094] In this embodiment, a nickel-based single-crystal superalloy is prepared, and its chemical composition is shown in Table 1. The difference between this embodiment and Embodiment 1 lies in the different chemical compositions. Other preparation steps and parameters are the same as those in Embodiment 1.

[0095] Embodiment 5

[0096] In this embodiment, a nickel-based single-crystal superalloy is prepared, and its chemical composition is shown in Table 1. The difference between this embodiment and Embodiment 1 lies in the different chemical compositions. Other preparation steps and parameters are the same as those in Embodiment 1.

[0097] Comparative Example 1

[0098] Comparative Example 1 provides a nickel-based single-crystal superalloy, and its chemical composition is shown in Table 1. In Comparative Example 1: (Co + W + Ta) / (Mo + Cr) = 3.7, which does not meet the range required by the present invention.

[0099] Other preparation steps and parameters are the same as those in Embodiment 1.

[0100] Comparative Example 2

[0101] Comparative Example 2 provides a nickel-based single-crystal superalloy, and its chemical composition is shown in Table 1. The main difference between Comparative Example 2 and Embodiment 1 is that the heat treatment regime is different. The heat treatment regime of Comparative Example 2 is as follows: solution treatment conditions: 1285 °C / 6 h, AC (air cooling); aging treatment method: 1080 °C / 6 h, AC + 870 °C / 24 h, AC (air cooling), and the heat treatment regime does not meet the range required by the present invention.

[0102] Other preparation steps and parameters are the same as those in Embodiment 1.

[0103] Comparative Example 3

[0104] Comparative Example 3 provides a nickel-based single-crystal superalloy, and its chemical composition is shown in Table 1. In Comparative Example 1: (Co + W + Ta) / (Mo + Cr) = 2.79, which does not meet the range required by the present invention.

[0105] Other preparation steps and parameters are the same as those in Embodiment 1.

[0106] Table 1 is a list of the chemical composition of the alloys (Embodiments 1 - 5, Comparative Examples 1 - 3) of the present invention and Rene N5 (wt.%)

[0107] Table 1

[0108]

[0109] Note: The meaning of "balance" in the Ni content column in the table is "remainder".

[0110] Table 2 compares the γ / γ′ phase interface energy, tensile strength at 1100℃, and creep life at 1100℃ / 137MPa of the alloys of the present invention (Examples 1-5, Comparative Examples 1-3) and Rene N5 after heat treatment.

[0111]

[0112] The nickel-based single-crystal superalloys prepared in Examples 1-5 and Comparative Examples 1-3 were characterized, and the characterization results are as follows:

[0113] The microstructure of the heat-treated nickel-based single-crystal superalloy prepared in Example 1 is as follows: Figure 1 As shown, from Figure 1 It can be seen that the nickel-based single-crystal superalloy of the present invention has a cubic γ′ phase.

[0114] The γ / γ′ phase interface mismatch of the heat-treated nickel-based single-crystal superalloy prepared in Example 2 is as follows: Figure 2 As shown. The nickel-based single-crystal superalloy of the present invention has a small mismatch degree and a high degree of coherence between the γ and γ′ phases.

[0115] A comparison of the γ / γ′ interfacial energies of the heat-treated nickel-based single-crystal superalloys prepared in Example 3 and typical heat-treated second-generation nickel-based single-crystal superalloys Rene N5, CMSX-4, PWA1484, and DD406 is shown in the figure. Figure 3 .from Figure 3 It can be seen that the γ / γ′ phase interface energy of the nickel-based single-crystal superalloy of the present invention is lower than that of the traditional second-generation single-crystal superalloy.

[0116] A comparison of Larson-Miller curves of the heat-treated nickel-based single-crystal superalloy prepared in Example 4 and the typical heat-treated second-generation nickel-based single-crystal superalloy Rene N5 is shown in the figure. Figure 4 .from Figure 4 It can be seen that the creep performance of the nickel-based single-crystal superalloy of the present invention is significantly higher than that of the Rene N5 alloy.

[0117] The creep properties of the heat-treated nickel-based single-crystal superalloy prepared in Example 5 after different long-term heat exposures at 900°C are shown in the figure. Figure 5 As shown. From Figure 5 It can be seen that the performance of the alloy of the present invention did not deteriorate after long-term heat exposure, and the alloy had the best creep performance after 300 hours of heat exposure.

[0118] Figure 6 The microstructure of the heat-treated nickel-based single-crystal superalloys prepared in Example 1 and Comparative Example 1 after holding at 1100℃ for 200h is shown below. Figure 6It can be seen that the alloy composition of this invention, satisfying (Co+W+Ta) / (Mo+Cr) = 2.9~3.1, results in a lower interphase interface energy and a lower γ′ phase rafting rate. Even after 200 hours, the non-rafted γ′ phase can still be observed, demonstrating excellent high-temperature structural stability. In contrast, the γ′ phase rafting rate in Comparative Example 1 is faster, which is detrimental to improving high-temperature performance.

[0119] Figure 7 The microstructure of the heat-treated nickel-based single-crystal superalloys prepared in Example 1 and Comparative Example 2 after being held at 1100℃ for 200h is shown. It can be seen that the heat treatment regime of Comparative Example 2 does not meet the requirements of the invention and cannot effectively control element diffusion and element occupancy. Therefore, the alloy interface energy is high and the domain boundary energy of the opposite phase γ′ is low. As a result, the stability of the alloy microstructure decreases and rafting occurs earlier.

[0120] Figure 8 The microstructures of the heat-treated nickel-based single-crystal superalloys prepared in Example 1 and Comparative Example 3 after holding at 1100℃ for 300 h are shown. Because the Cr content in Comparative Example 3 is relatively high, its alloy composition (Co+W+Ta) / (Mo+Cr) = 2.79, which does not satisfy (Co+W+Ta) / (Mo+Cr) = 2.9–3.1. The increased Cr content leads to a higher distribution ratio of W and Mo on the matrix side of the phase interface, resulting in a higher phase interface mismatch and an increased γ′ phase rafting rate. Compared to Example 1, Comparative Example 3 is more prone to γ′ phase rafting, which is detrimental to improving high-temperature performance.

[0121] The most significant aspect of this invention is that it reduces the interfacial energy of the alloy through compositional design. This reduction in interfacial energy significantly improves the stability of the alloy's microstructure; that is, under high-temperature loading, the γ' phase rafting rate is slower or even non-rafting occurs. Figure 6 As shown. The alloy of this invention achieves high strength through interface strengthening.

[0122] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Any simple modifications, equivalent changes, and alterations made to the above embodiments based on the technical essence of the present invention shall still fall within the scope of the technical solution of the present invention.

Claims

1. A nickel-based single-crystal superalloy, characterized in that, The nickel-based single-crystal superalloy comprises the following chemical components by weight percentage: Cr: 6-8 wt%, Co: 7-9 wt%, Mo: 2-3 wt%, W: 8-9 wt%, Ta: 5-7 wt%, Al: 5-7 wt%, Ti: 1-2 wt%, C: 0-0.05 wt%, balance Ni; The sum of the percentage contents of Co, W, and Ta is A; the sum of the percentage contents of Mo and Cr is B; and A / B = 2.9 to 3.

1.

2. The nickel-based single-crystal superalloy according to claim 1, characterized in that, The nickel-based single-crystal superalloy comprises the following chemical components by weight percentage: Cr: 6.0~7.8wt%, Co: 7.5~8.9wt%, Mo: 2.0~2.6wt%, W: 8.3~8.9wt%, Ta: 5.5~6.8wt%, Al: 5.3~6.7wt%, Ti: 1.7~1.8wt%, C: 0.02~0.04wt%, the balance is Ni.

3. The nickel-based single-crystal superalloy according to claim 1 or 2, characterized in that, In the nickel-based single-crystal superalloy: the number of electron vacancies N v ≤2.

3.

4. The nickel-based single-crystal superalloy according to any one of claims 1-3, characterized in that, In the nickel-based single-crystal superalloy, the weight percentage of impurity elements meets the following requirements: O≤0.001wt%, N≤0.001wt%, S≤0.001wt%, Zr≤0.0055wt%, Mn≤0.01wt%, Si≤0.005wt%, P≤0.005wt%, Cu≤0. 05wt%, Mg≤0.008wt%, Se≤0.0002wt%, Pb≤0.0002wt%, Te≤0.00005wt%, Bi≤0.00002wt%, Sn≤0.0015wt%.

5. The nickel-based single-crystal superalloy according to any one of claims 1-4, characterized in that, If the nickel-based single-crystal superalloy is in a heat-treated state, then the γ / γ′ interfacial energy E in the nickel-based single-crystal superalloy is less than 5 × 10⁻⁶. -2 J / m 2 The γ′ opposite domain boundary energy is >250 mJ / m 2 .

6. The nickel-based single-crystal superalloy according to any one of claims 1-5, characterized in that, The nickel-based single-crystal superalloy is a Re-free second-generation single-crystal superalloy; and / or If the nickel-based single-crystal superalloy is in a heat-treated state, then the creep rupture life of the nickel-based single-crystal superalloy under the conditions of 1100℃±5℃ and 137MPa±5MPa is >150h; and / or If the nickel-based single-crystal superalloy is in a heat-treated state, the γ′ phase remains cubic after heat exposure treatment at 900-1100℃ for 200-300 hours, thus improving its creep life. More preferably, before heat exposure, the creep life of the nickel-based single-crystal superalloy at 1100℃±2℃ and 127MPa±2MPa is 120h±10h, and after heat exposure treatment, the creep life of the nickel-based single-crystal superalloy at 1100℃±2℃ and 127MPa±2MPa is 150h±10h.

7. The method for preparing the nickel-based single-crystal superalloy according to any one of claims 1-6, characterized in that, The preparation method includes the following steps: Vacuum induction melting step: The raw materials are subjected to vacuum induction melting and cast into master alloy ingots; The steps for preparing single-crystal alloys are as follows: the master alloy ingot is remelted by high-speed solidification or liquid metal cooling, and then directional solidification is performed by spiral crystal selector or seed crystal method to obtain cast nickel-based single-crystal high-temperature alloy. Heat treatment: The cast nickel-based single-crystal superalloy is subjected to heat treatment to obtain a heat-treated nickel-based single-crystal superalloy.

8. The method for preparing nickel-based single-crystal superalloys according to claim 7, characterized in that, In the vacuum induction melting step: the raw materials include elemental Ni, elemental Co, elemental Cr, elemental W, elemental Mo, elemental Ta, elemental Ti, elemental Al, and elemental C; and / or In vacuum induction melting, the refining temperature is 1550±10℃, the refining time is 20~40min, and the vacuum degree during refining is ≤5Pa.

9. The method for preparing a nickel-based single-crystal superalloy according to claim 7, characterized in that, In the steps described for preparing single-crystal alloys: The pouring temperature is 1530–1560℃; and / or The directional solidification pulling rate is 3–7 mm / min.

10. The method for preparing a nickel-based single-crystal superalloy according to claim 7, characterized in that, The heat treatment steps include: Solution treatment steps: The as-cast nickel-based single crystal high-temperature alloy is first heated to 1285-1295℃ and held for 2-3 hours, then heated to 1295-1300℃ and held for 2-5 hours, then heated to 1325-1350℃ and held for 3-5 hours, and then cooled to obtain the solution-treated nickel-based single crystal high-temperature alloy. Aging treatment steps: The solution-treated nickel-based single-crystal superalloy is first heated to 1085-1095℃, held for 5-7 hours, and then cooled to room temperature; then heated to 850-879℃, held for 22-26 hours, and cooled to obtain the heat-treated nickel-based single-crystal superalloy.